2017
DOI: 10.3389/fnagi.2017.00329
|View full text |Cite
|
Sign up to set email alerts
|

Random Forest Algorithm for the Classification of Neuroimaging Data in Alzheimer's Disease: A Systematic Review

Abstract: Objective: Machine learning classification has been the most important computational development in the last years to satisfy the primary need of clinicians for automatic early diagnosis and prognosis. Nowadays, Random Forest (RF) algorithm has been successfully applied for reducing high dimensional and multi-source data in many scientific realms. Our aim was to explore the state of the art of the application of RF on single and multi-modal neuroimaging data for the prediction of Alzheimer's disease.Methods: A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
294
0
9

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 473 publications
(307 citation statements)
references
References 41 publications
4
294
0
9
Order By: Relevance
“…The heterogeneity in clinical presentation, the dispersion we observed in mitochondrial physiology, and their correlation lend support to the hypothesis that there may be subgroups of different mitochondrial phenotypes correlating with the symptomatology in the general population of idiopathic PD patients. To test this possibility, we used machine‐learning methodology and recursive partitioning to build a CART, which have been successfully used in applications such as clinical subtypes classification and neuroimaging data analysis to predict Alzheimer's disease …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The heterogeneity in clinical presentation, the dispersion we observed in mitochondrial physiology, and their correlation lend support to the hypothesis that there may be subgroups of different mitochondrial phenotypes correlating with the symptomatology in the general population of idiopathic PD patients. To test this possibility, we used machine‐learning methodology and recursive partitioning to build a CART, which have been successfully used in applications such as clinical subtypes classification and neuroimaging data analysis to predict Alzheimer's disease …”
Section: Resultsmentioning
confidence: 99%
“…To test this possibility, we used machine-learning methodology and recursive partitioning to build a CART, 25 which have been successfully used in applications such as clinical subtypes classification 26 and neuroimaging data analysis to predict Alzheimer's disease. 27 All available parameters-that is, demographic variables (ie, age, age at onset, duration of the disease, and gender), the equivalent of levodopa medication, respirometry, and acidification parameters-were used in the CART process as input variables to predict either the SENS-PD or the MDS-UPDRS III (ie, response variables). Intrinsic to CART modeling is a selection step that eliminates in an unbiased fashion redundancy among the input variables to identify the most significant parameters.…”
Section: Unbiased Grouping Of Patients On the Basis Of Laboratory Andmentioning
confidence: 99%
“…A disadvantage of the RF is its sensitivity to the input parameters (Huang & Boutros, 2016). RFs have been widely applied both in bioinformatics (Qi, 2012) and in neuroimaging (Sarica, Cerasa, & Quattrone, 2017).…”
Section: Random Forestmentioning
confidence: 99%
“…The experimental results suggested that linear kernels are preferable in this application and that SVMs seem to be robust against different preprocessing strategies, although the most evident effect is observed with the detrending of input time series. Another popular classifier is RF (Sarica et al, 2017). Fratello et al (2017) propose a multiview approach (see Box 1) for the classification of subjects affected by neurodegenerative diseases, specifically Amyotrophic Lateral Sclerosis and Parkinson's Disease.…”
Section: Patient Classification From Neuroimaging Datamentioning
confidence: 99%
“…Multidimensionality of aforementioned clinical diagnostic factors makes it difficult for us to analyze and infer the information from the same. In this regard, a review describing a computer-based diagnostic method using Random Forest (RF) algorithms on medical imaging data have demonstrated high reliability in classifying early stage MCI patients which later progresses to advanced stages of AD [4]. Similarly, multi-kernel Support Vector Machine (SVM) was employed to predict future clinical symptoms of MCI patients using both baseline and longitudinal multimodal biomarkers data [5].…”
Section: Introductionmentioning
confidence: 99%